Advokasi Ketahanan Pangan di Kabupaten Muaro Jambi - Gina Fauzia; Elwamendri Elwamendri; Siti Kurniasih; Rozaina Ningsih; Fendria Sativa (Jurnal Pemberdayaan Umat, 2023)
Purpose: This research aims to provide knowledge and asisstance small area with very potential local resources. This service is to provide knowledge and assistance in increasing the capacity of farmer groups in utulizing local resources in realizing food security in Muaro Jambi Regency. Methodology: The method used in counseling, mentoring and action in implemnting fod security. The location that became the focus of the acrtivity was Setiris Village, Maro Sebo Distruct Muaro Jambi Regency, the location selection was based on consideration of the potential of natural resources that had not been utilizied by the village community. Results: The results of thi activity are (1) some of the paddy fields that have been used for lowland rice farming, where from an area of 3 ha has increased to 6 ha of cultivated rice fields now. With the pilot conducted on several plots, it convinces farmers to rework their paddly fields, (2) increasing the planting Index, the planting index that was previously only 100 farmers has now increased to 200, where in September 2022 harvest and replant in November 2022, (3) the emergence of awareness of farmers in dependence on the use of chemical fertilizer, where farmers are currently trying to produce JAKABA. Conclusion: Food security is a central isuue in the framework of africulture and national development. One of the government programs that has been launched is “NAWACITA” which builds and srtengthens small areas with very potential local resource.